ANALYSIS OF PROFITABILITY OF AGRICULTURAL ENTERPRISES AS AN INDICATOR OF ECONOMIC EFFICIENCY - DVORNYK, INNA; STADNYK, VIKTORIYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Agriculture in Ukraine is a promising branch of the national economy, as it has the main factors of production - land and labor. Most agricultural products produce medium-sized agricultural enterprises, most often farms. Profitability is an indicator that means not only reimbursement of costs associated with the production and sale of products, but also profit. It is determined that the economic efficiency of agricultural enterprises is directly influenced by the organizational and legal form of management, size, direction of specialization, cost of production, resource supply. Profitable is the production of such agricultural products: sunflower, milk, potatoes, cereals and leguminous crops. In order to increase the efficiency of the functioning of agricultural enterprises, it is proposed to: provide preferential long-term lending to agricultural producers; to stimulate the efficiency of state-owned enterprises; take measures to prevent excessive concentration of land resources in the ownership of individual enterprises.